2005
DOI: 10.1542/peds.2005-0386
|View full text |Cite
|
Sign up to set email alerts
|

Worse Quality of Life for Children With Newly Diagnosed Attention-Deficit/Hyperactivity Disorder, Compared With Asthmatic and Healthy Children

Abstract: ABSTRACT. Objective. To evaluate the quality of life (QOL) of untreated children with newly diagnosed attention-deficit/hyperactivity disorder (ADHD), compared with asthmatic and healthy children.Methods. This prospective, case-control study included a group of 120 children, 6 to 12 years of age, with newly diagnosed ADHD according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. Subjects were matched according to age, gender, and health care area with 2 control groups, ie, 93 asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
105
2
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(132 citation statements)
references
References 17 publications
9
105
2
15
Order By: Relevance
“…A recently reported prospective case-control study conducted in Spain found that untreated children with newly diagnosed ADHD had a worse quality of life than healthy children or children with newly diagnosed asthma [10]. Not surprisingly, the quality of life among children with ADHD worsened as the severity of ADHD symptoms increased and with the presence of co-morbid psychiatric disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…A recently reported prospective case-control study conducted in Spain found that untreated children with newly diagnosed ADHD had a worse quality of life than healthy children or children with newly diagnosed asthma [10]. Not surprisingly, the quality of life among children with ADHD worsened as the severity of ADHD symptoms increased and with the presence of co-morbid psychiatric disorders [21].…”
Section: Introductionmentioning
confidence: 99%
“…Estes comportamentos podem manifestar-se ao longo dos primeiros anos de vida, denominado tríade sintomatológica, destacando-se a desatenção, hiperatividade e impulsividade. Tais características, segundo Escobar et al (2005) causam problemas no seu desenvolvimento em vários domínios relativos a integração social, a noção de tempo, a aquisição da linguagem e também ao desenvolvimento motor.…”
Section: Introductionunclassified
“…The symptoms of ADHD may interfere with a person's ability to conduct normal daily activities. ADHD is associated with broad impairment in many Health Related Quality of Life (HRQoL) parameters, including academic performance, behaviour at school, peer relations and family function [5]. Studies have indicated that, compared to their peers without ADHD, young people with ADHD also exhibit higher levels of comorbidity with other psychiatric disorders as oppositional defiant disorder, conduct disorder, anxiety disorder and depression, and with somatic conditions as asthma [2].…”
Section: Introductionmentioning
confidence: 99%
“…Escobar et al showed that ADHD interferes to an even greater extent than asthma with the daily lives of children, parents and families, primarily in areas related to psychosocial functioning [5].…”
Section: Introductionmentioning
confidence: 99%